Liability Derived from Unknown Debt - Ahmad Baqeri; Zohreh Nik Amal (آموزه‌‌های فقه مدني, 2012)
According to almost majority of Shia’s jurists, guarantor can guarantee the debt of a debtor without being aware of his debt, even if its amount is higher than he thought. Following Shia’s jurists, the Civil Law in Article 694 has also expressed clearly that it is not necessary to know the quantity, qualities and circumstances of the debt that he warrants. In contrary, the opponents have referred to the evidences such as negation of the risk, inaccuracy of commitment to the financial health in the case of ignorance. In this paper we have considered the reasons of those who believe in invalidation of this claim and it has been rejected, but the view of those who believe in its validity has been proven. Jurisprudents, who believe in accuracy of liability of the unknown debt, have provided it to the possibility of knowing it after contract of liability and if it is not possible to know the amount of the debt, it will be invalid. Acknowledging this condition, this paper has criticized the idea of jurists and legislators that the liability of unknown debt is invalid. Thus, it has been suggested that the second part of the Article 694 of the Civil Code be removed.